Serum Levels of Brain-Derived Neurotrophic Factor and Insulin-Like Growth Factor 1 Are Associated With Autonomic Dysfunction and Impaired Cerebral Autoregulation in Patients With Epilepsy - Chen, Shu-Fang; Jou, Shuo-Bin; Chen, Nai-Ching; Chuang, Hung-Yi; Huang, Chi-Ren; Tsai, Meng-Han; Tan, Teng-Yeow; Tsai, Wan-Chen; Chang, Chiung-Chih; Chuang, Yao-Chung (Frontiers in Neurology, 2018)
Background: Brain-derived neurotrophic factor (BDNF) and insulin-like growth factor 1 (IGF-1) may regulate the autonomic nervous system (ANS) in epilepsy. The present study investigated the role of IGF-1 and BDNF in the regulation of autonomic functions and cerebral autoregulation in patients with epilepsy. Methods: A total of 57 patients with focal epilepsy and 35 healthy controls were evaluated and their sudomotor, cardiovagal, and adrenergic functions were assessed using a battery of ANS function tests, including the deep breathing, Valsalva maneuver, head-up tilting, and Q-sweat tests. Cerebral autoregulation was measured by transcranial doppler during the breath-holding test and the Valsalva maneuver. Interictal serum levels of BDNF and IGF-1 were measured with enzyme-linked immunosorbent assay kits. Results: During interictal period, reduced serum levels of BDNF and IGF-1, impaired autonomic functions, and decreased cerebral autoregulation were noted in patients with epilepsy compared with healthy controls. Reduced serum levels of BDNF correlated with age, adrenergic and sudomotor function, overall autonomic dysfunction, and the autoregulation index calculated in Phase II of the Valsalva maneuver, and showed associations with focal to bilateral tonic-clonic seizures. Reduced serum levels of IGF-1 were found to correlate with age and cardiovagal function, a parameter of cerebral autoregulation (the breath-hold index). Patients with a longer history of epilepsy, higher seizure frequency, and temporal lobe epilepsy had lower serum levels of IGF-1. Conclusions: Long-term epilepsy and severe epilepsy, particularly temporal lobe epilepsy, may perturb BDNF and IGF-1 signaling in the central autonomic system, contributing to the autonomic dysfunction and impaired cerebral autoregulation observed in patients with focal epilepsy.